2018
DOI: 10.1042/bst20170108
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase-like proteins as regulators of innate immunity and tissue repair: helpful lessons for asthma?

Abstract: Chitinases and chitinase-like proteins (CLPs) belong to the glycoside hydrolase family 18 of proteins. Chitinases are expressed in mammals and lower organisms, facilitate chitin degradation, and hence act as host-defence enzymes. Gene duplication and loss-of-function mutations of enzymatically active chitinases have resulted in the expression of a diverse range of CLPs across different species. CLPs are genes that are increasingly associated with inflammation and tissue remodelling not only in mammals but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 112 publications
(131 reference statements)
0
44
0
1
Order By: Relevance
“…Other members of the chitinase family, such as chitinase-3-like protein 1 (CHI3L1) or chitinase-3-like protein 2 (CHI3L2), bind chitin but do not exhibit enzymatic activity 11. Recent evidence implicates chitinases in regulating the innate immune system12 and modulating inflammation during the progression of many diseases 13. Given that chitinases are expressed by activated microglia and/or astrocytes in the central nervous system (CNS), these biomarkers may be reflective of glial activation.…”
Section: Introductionmentioning
confidence: 99%
“…Other members of the chitinase family, such as chitinase-3-like protein 1 (CHI3L1) or chitinase-3-like protein 2 (CHI3L2), bind chitin but do not exhibit enzymatic activity 11. Recent evidence implicates chitinases in regulating the innate immune system12 and modulating inflammation during the progression of many diseases 13. Given that chitinases are expressed by activated microglia and/or astrocytes in the central nervous system (CNS), these biomarkers may be reflective of glial activation.…”
Section: Introductionmentioning
confidence: 99%
“…Chil3 (also known as YKL-40 in humans and BRP-39 in mice) does not contain known chitinase activity, though it has been implicated in host defense, inflammation, and remodeling processes 73,74 . Chil3 has been reported as a biomarker for skin wound infection 96 , cardiovascular disease and diabetes 97 , and cancer 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Chil3 is a member of the mammalian chitinase family that lacks the chitinase activity though it is highly secreted by macrophages and neutrophils 71,72 . Similar to the function of S100 proteins, chitinase-like proteins have also been shown to be mediators of inflammation and antimicrobial responses in multiple models of disease such as asthma and pulmonary fibrosis as well as involved in tissue remodeling and wound healing [73][74][75] . In previous work in kidney disease models, a urinary proteomic study has shown that chitinases-like proteins could be candidate biomarkers for S-AKI 75 .…”
Section: Discovery-based Studies Recapitulate Signature Proteins For mentioning
confidence: 99%
“…Elevated levels of CHI3L1 and CHI3L2 have been shown to drive proliferation of a number of human cells (28,30,32,33,42) and are associated with numerous chronic inflammatory diseases (e.g. arthritis and asthma (43)(44)(45) and poor prognosis of several cancers including glioblastoma, nonsmall-cell lung cancer and colorectal cancer (46)(47)(48)(49)(50). Interestingly, in the case of colorectal cancer, downregulation of DIS3L2 (as a consequence of knockdown of lncRNA AC105461.1) enhances the proliferation and stem-cell like properties of cells of the colorectal cancer line SW480 (51).…”
Section: Idgf2 Is a Conserved Member Of The Chitinase-like Family Witmentioning
confidence: 99%